Job Satisfaction among Correctional Officers in Iceland - Sigurbjörg Ólína Jónsdóttir 1990- (2018)
Job satisfaction among correctional officers can have a great impact on how successful operations in prisons are. Previous studies have shown that some factors have more impact on job satisfaction than others. The aim of present study was to examine job satisfaction among correctional officers in Iceland and find factors that affected the job satisfaction. Correctional officers working in all five prisons in Iceland were invited to participate, 63 of 93 officers participated, a response rate of 67.7%. A questionnaire was sent to all prisons by mail, it consisted of the DASS stress scale and questions about background, job satisfaction, and job loyalty. Participants reported, on average, that they were rather satisfied with their job. However, job satisfaction among correctional officers seems to be lower than among employees in many other professions in Iceland. A path analysis based on two-step multiple linear regression with two dependent variables, one at a time, indicated that one of the two dependent variables, job satisfaction, was significantly related to conditions in the working environment, employees trust towards the executive board of the organization, and employees stress level. The other dependent variable, job loyalty, was significantly related to four factors, including the job satisfaction. Starfsánægja meðal fangavarða getur haft áhrif á hversu vel starfsemi innan fangelsa gengur. Rannsóknir hafa sýnt að ákveðnir þættir geta haft meiri áhrif á starfsánægju en aðrir þættir. Markmið þessarar rannsóknar var að skoða starfsánægju fangavarða á Íslandi og finna þætti sem höfðu áhrif á starfsánægjuna. Fangaverðir sem unnu í öllum fimm fangelsunum á Íslandi var boðið að taka þátt í rannsókninni, 63 af 93 fangavörðum tóku þátt, svarhlutfallið var 67,7%. Spurningalisti var sendur í öll fangelsin með pósti, hann samanstóð af DASS steitu skalanum og spurningum tengdum bakgrunni, starfsánægju og starfstryggð. Þátttakendur svöruðu, að meðaltali, að þeir væru fremur ánægðir í starfi sínu. Samt sem áður, ...